2007
DOI: 10.1080/08880010701394998
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Repositioning of the Contralateral Testicle Before Irradiation of a Paratesticular Rhabdomyosarcoma for Preservation of Hormone Production

Abstract: Little has been published so far about the possibility of preserving an uninvolved testicle by surgically transferring it out of the irradiation field. A then 16-year-old boy developed a right paratesticular embryonal rhabdomyosarcoma in 2003. Initial treatment consisted of orchiectomy and chemotherapy. Prior to local radiotherapy, the contralateral testicle was surgically transferred into the left groin region. Hyperfractionated, accelerated radiation therapy was administered to a total dose of 44.0 Gy. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…There are several clinical cases reported in the literature, the first dating back to more than 30 years ( 76 ), in which a testicular transposition was performed to protect the residual gonad from adjuvant radiotherapy treatment. The healthy testis was transposed at the inguinal ( 77 ), abdominal ( 78 ) or leg region ( 79 ) and then repositioned in the scrotum at the end of therapy. It is interesting to note that in one clinical case report ( 80 ), the testis was able to resume spermatogenesis during the following months after post-traumatic repositioning in a subcutaneous pocket at tight level.…”
Section: Surgical Approaches To Preserve Testicular Functionmentioning
confidence: 99%
“…There are several clinical cases reported in the literature, the first dating back to more than 30 years ( 76 ), in which a testicular transposition was performed to protect the residual gonad from adjuvant radiotherapy treatment. The healthy testis was transposed at the inguinal ( 77 ), abdominal ( 78 ) or leg region ( 79 ) and then repositioned in the scrotum at the end of therapy. It is interesting to note that in one clinical case report ( 80 ), the testis was able to resume spermatogenesis during the following months after post-traumatic repositioning in a subcutaneous pocket at tight level.…”
Section: Surgical Approaches To Preserve Testicular Functionmentioning
confidence: 99%
“…Testicular tissue is exquisitely sensitive to radiation‐induced damage, so the proximity of the normal contralateral testis would place it at risk of radiation damage if not moved out of the RT field 26 . Several small case studies including 11 prepubertal or postpubertal patients have reported a normal‐sized testis, normal testosterone levels (four of five evaluated) and fertility (one reported) after temporary testicular transposition 27,28 . A recent study of 12 children undergoing testicular transposition before scrotal external radiotherapy reported that six of nine children evaluated had normal testosterone levels for their age, while more follow‐up would be needed to assess their fertility 29 .…”
Section: Consensus Surgical Opinionmentioning
confidence: 99%
“…If a previous trans-scrotal biopsy has been performed, or if there is local invasion of the tumor into the scrotal skin, hemi-scrotectomy is indicated (Dall'Igna et al 2003). If radiation therapy to the area is required, such as for residual disease or local relapse, the contralateral testicle can be temporarily transposed out of the treatment field to a subcutaneous pocket on the adjacent thigh or inguinal canal (Gruschow et al 2007). These tumors have a high incidence of lymphatic spread, and all patients should be evaluated with a CT scan of the abdomen and pelvis to evaluate for enlarged retroperitoneal lymph nodes.…”
Section: Genitourinarymentioning
confidence: 99%